Study of Antibacterial Activity and Viability of Lactic Acid Bacteria (BAL) on Fermented Milk Beverage Products Circulating in Malang City - Angga Bian Permana (Contributions of Central Research Institute for Agriculture, 2021)
The results showed that eight brands of fermented milk drinks circulating in Malang City showed 6 brands of fermented milk drinks namely brands SF1, SF2, SF3, SF4, SF5, and SF6 containing live lactic acid bacteria cultures in their products. Meanwhile, the SF7 and SF8 brands do not contain live lactic acid bacteria cultures in their products. Fermented milk drink is a form of probiotic food which has long been known as a carrier food for probiotic organisms. Probiotics are food supplements in the form of live microbes that have beneficial effects on the human body by balancing microbes in digestion. Viability and functional activity of probiotics is an important thing in a probiotic supplement product. One of the functional activities of this probiotic food is the ability of the bacterial culture in it to inhibit the growth and activity of bacteria that are pathogenic to the body. showed that fermented milk drinks that had live and active cultures had higher antibacterial activity when compared to fermented milk drinks that did not have probiotic bacterial cultures in them. SF2 brand fermented milk drink has a higher activity of inhibiting the growth of pathogenic Staphylococcus aureus bacteria when compared to other brands. As for the inhibition of Escherichia coli pathogenic bacteria, fermented milk drink brand SF3 has the highest antibacterial activity.